2016
DOI: 10.1097/igc.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oncologic and Reproductive Outcomes in Young Women With Early Endometrial Cancer Conservatively Treated: A Prospective Study and Literature Update

Abstract: After a long follow-up, combined HR and LNG-IUD would seem to improve the efficacy of progestin alone. High pregnancy and live birth rates were observed in women attempting to conceive. This approach is still experimental and should be offered only in the framework of scientific protocols conducted in cancer centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…HR also helps improve the efficacy of progestogen due to less tumor burden. As a result, a higher regression rate and a shorter time between diagnosis and regression [ 72 ]. Some complication of HR such as endometrial destruction, intrauterine adhesion, which can affect the reproductive outcomes of young patients desire to preserve their fertility as mentioned before [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HR also helps improve the efficacy of progestogen due to less tumor burden. As a result, a higher regression rate and a shorter time between diagnosis and regression [ 72 ]. Some complication of HR such as endometrial destruction, intrauterine adhesion, which can affect the reproductive outcomes of young patients desire to preserve their fertility as mentioned before [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, diagnostic hysteroscopy can found the uterine synechia caused by serial dilation and curettage (D&C) at follow-up and operate hysteroscopic adhesiolysis [ 22 ]. A recent prospective study focused on HR and progestin therapy reached a live birth rate of 50% in all treated patients and 86.6% for women who tried to conceive with no complications [ 72 ]. Another problem may be the dissemination of cancerous cells into the peritoneal cavity during hysteroscopy, it is reported that it didn't risk recurrence rate and the long-term prognosis is unclear [ 16 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the medroxyprogesterone acetate dose to 1000 mg was considered if the patient had 6 to 9 months of persistent disease in follow-up D&Cs. Recurrence was diagnosed if carcinoma was observed on pathology after complete remission 30. An anti-adhesive medication (poloxamer) was used in the endometrial cavity every time D&C was performed 31 32.…”
Section: Methodsmentioning
confidence: 99%
“…Hysteroscopic resection (HR) was performed using a 5 mm cutting loop electrode to resect (1) the tumor lesion, (2) the endometrium adjacent to the tumor, (3) the myometrium underlying the tumor. The hysteroscopic procedure is further detailed in our previous paper [6]. If final pathology confirmed a G1 endometrioid EC with no myometrial invasion and PR positivity at immunohistochemistry, hormone therapy was started 1 week after HR.…”
Section: Methodsmentioning
confidence: 99%